The Effect Of Good Corporate Governance, Work Life Balance, Talent Management And Person Organization Fit On Employee Performance At The Planning, Research And Development Agency Of Bukittinggi City - Robby Dharma; Lestari Gusnawati (UPI YPTK Journal of Business and Economics, 2022)
The purpose of this research journal is to find out how much "The Influence of Good Corporate Governance, Work Life Balance, Talent Management and Person Organization Fit on Employee Performance at the Planning, Research and Development Agency (Bapelitbang) of Bukittinggi City. Methods of collecting data through surveys, interviews, and questionnaires with a sample of 34 respondents.The analytical method used is Multiple Linear Regression Analysis.The results of data analysis concluded, partially there is a positive and significant effect of Good Corporate Governance on Employee Performance. Partially there is a positive and significant effect of work life balance on employee performance. Partially there is a positive and significant influence of Talent Management on Employee Performance. Partially there is a positive and significant effect of Personorganization Fit on Employee Performance. Simultaneously there is a positive and significant influence of Good Corporate Governance, Work Life balance, Talent Management, Personorganization Fit on Employee Performance. The contribution of Good Corporate Governance, Work Life balance, Talent Management, Personorganization Fit variables is 0.641 or 64.1% while the remaining 35.9% is influenced by other variables